Root high‐affinity K+ and Cs+ uptake and plant fertility in tomato plants are dependent on the activity of the high‐affinity K+ transporter SlHAK5. (26th April 2020) - Nieves‐Cordones, Manuel; Lara, Alberto; Silva, Martha; Amo, Jesús; Rodriguez‐Sepulveda, Pascual; Rivero, Rosa M.; Martínez, Vicente; Botella, M. Angeles; Rubio, Francisco
Abstract: Root K + acquisition is a key process for plant growth and development, extensively studied in the model plant Arabidopsis thaliana . Because important differences may exist among species, translational research supported by specific studies is needed in crops such as tomato. Here we present a reverse genetics study to demonstrate the role of the SlHAK5 K + transporter in tomato K + nutrition, Cs + accumulation and its fertility. slhak5 KO lines, generated by CRISPR‐Cas edition, were characterized in growth experiments, Rb + and Cs + uptake tests and root cells K + ‐induced plasma membrane depolarizations. Pollen viability and its K + accumulation capacity were estimated by using the K + ‐sensitive dye Ion Potassium Green 4. SlHAK5 is the major system for high‐affinity root K + uptake required for plant growth at low K +, even in the presence of salinity. It also constitutes a pathway for Cs + entry in tomato plants with a strong impact on fruit Cs + accumulation. SlHAK5 also contributes to pollen K + uptake and viability and its absence produces almost seedless fruits. Knowledge gained into SlHAK5 can serve as a model for other crops with fleshy fruits and it can help to generate tools to develop low Cs + or seedless fruits crops. Abstract : The K + transporter SlHAK5 from tomato plays a crucial role in K + nutrition, in particular under saline conditions, and in the accumulation of Cs + in vegetative tissues and in fruits. Moreover, slhak5 fruits have few seeds which are related to SlHAK5 contribution to pollen K + uptake and viability.